Academic Supervision To Enhance Teachers' Tpack Competence - Khasanah, Nurul Uswatun; Fatoni, Achmad; Haryanto, Sigit; Assidiqi, Muadz (Perspektif Ilmu Pendidikan, 2023)
The objective of this study is to investigate, elucidate, and analyze the academic oversight provided by the school principal in enhancing the proficiency of Technological Pedagogical Content Knowledge (TPACK) among teachers at SMK N 1 Karanganyar. The present study employs a qualitative study methodology utilizing a case study methodology. The data has been obtained from the paperwork provided by the statistical data informant. Various data collection procedures encompass interviews, observations, documentation, and surveys. Data analysis involves the process of reducing data, presenting data, and deriving descriptive findings. Data authenticity is achieved through the utilization of source triangulation. The research findings demonstrate the significance of TPACK competency in enhancing the overall quality of the learning process. Furthermore, the use of academic supervision has the potential to enhance the proficiency of teachers in integrating technology, pedagogy, and content knowledge (TPACK). The TPACK supervision outcomes at SMK N 1 Karanganyar, yielding an average score of 4.72, are categorized as "excellent". The primary focus of this research is to improve the educators Technological Pedagogical Content Knowledge (TPACK) by developing their proficiency in Technological Knowledge (TK), Content Knowledge (CK), Pedagogical Knowledge (PK), Pedagogical Content Knowledge (PCK), Technological Content Knowledge (TCK), and Technological Pedagogical Knowledge (TPK). The objective is to investigate how these abilities contribute to the enhancement of learning outcomes within the classroom setting.